2011
DOI: 10.1111/j.1863-2378.2009.01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Financial Effects of Hydatidosis in Cattle Slaughtered in Birre‐Sheleko and Dangila Abattoirs, Northwestern Ethiopia

Abstract: A cross-sectional survey of bovine hydatidosis was carried out on local zebu cattle slaughtered at Birre-Sheleko and Dangila Abattoirs from August 2007 to July 2008 to determine the prevalence and to estimate financial loss caused by the disease. Postmortem examination, hydatid cyst characterization and direct and indirect financial loss estimations were conducted. Out of the total of 521 animals examined (255 Birre-Sheleko and 266 Dangila), 79 (15.2%) were found harbouring one or more hydatid cyst. The preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
2
18
2
Order By: Relevance
“…In contrast to this, goats showed a low prevalence of 1.90 % hydatidosis which concurs with the findings of earlier workers in Debre Zeit (Adem 2006) and Addis Ababa (Marshet et al 2011). Moreover, there are also reports that reveal a higher prevalence of hydatidosis in sheep [22.2 % in Nekemte (Kumsa 1994), 29.3 % in Adama (Getaw et al 2010) and 19.9 % in Addis Ababa (Kebede et al 2011)] and goats [6.7 % in Adama (Getaw et al 2010), 16 % in Addis Ababa (Kebede et al 2010) and 8.99 % in Modojo (Abiyot et al 2011)]. The lower prevalence of cystic echinococcosis in sheep and goats in this study than most of the previous studies in different parts of Ethiopia indicated above might be due to variations in agroecology among different study sites, age and breed of study animals; stocking rates and movement of animals; animal husbandry systems, awareness, culture and religion of the society; and attitude to a number of dogs in different regions of country as has been suggested by Kumsa (1994) and Kebede et al (2010).…”
Section: Discussionsupporting
confidence: 64%
“…In contrast to this, goats showed a low prevalence of 1.90 % hydatidosis which concurs with the findings of earlier workers in Debre Zeit (Adem 2006) and Addis Ababa (Marshet et al 2011). Moreover, there are also reports that reveal a higher prevalence of hydatidosis in sheep [22.2 % in Nekemte (Kumsa 1994), 29.3 % in Adama (Getaw et al 2010) and 19.9 % in Addis Ababa (Kebede et al 2011)] and goats [6.7 % in Adama (Getaw et al 2010), 16 % in Addis Ababa (Kebede et al 2010) and 8.99 % in Modojo (Abiyot et al 2011)]. The lower prevalence of cystic echinococcosis in sheep and goats in this study than most of the previous studies in different parts of Ethiopia indicated above might be due to variations in agroecology among different study sites, age and breed of study animals; stocking rates and movement of animals; animal husbandry systems, awareness, culture and religion of the society; and attitude to a number of dogs in different regions of country as has been suggested by Kumsa (1994) and Kebede et al (2010).…”
Section: Discussionsupporting
confidence: 64%
“…This variation in prevalence of hydatidosis could be due to differences in animal husbandry system, back yard slaughtering of animals, lack of proper disposal of infected carcass and the presence of stray dogs and their relations with animals Mesele et al, (2013). In the present study, the overall prevalence of hydatidosis 22.13% is higher than 13.61% by melaku et al, (2012) in Dessie municipal abattoir, 15.2% as reported by Kebede et al, (2009b) in BirreSheleko and Dangila abattoirs, 16% in Wolaita Sodo abattoir by Kebede et al (2009a, c), 32.1% by Gebretsadik Berhe, (2009 in mekelle. These variations in prevalence of the diseases in different areas might be due to variation in the ecological factors that determine the occurrence of the diseases.…”
Section: Discussioncontrasting
confidence: 53%
“…For instance, annual financial losses ranging from U.S.$5059 to U.S.$138,000 have been reported in different endemic areas of Ethiopia including the Southern Nations, Nationalities, and People's Region (Bekele and Butako, 2011;Regassa et al, 2010;Kebede et al, 2009a), the Amhara Region (Kebede et al, 2011), and the Oromia Region (Getaw et al, 2010). Estimated losses per infected animal in Ethiopia varied from U.S.$1.6 to U.S.$21 (Kebede et al, 2009a,d).…”
Section: Economic Impact Of Cystic Echinococcosis In Production Animalsmentioning
confidence: 99%